ALMA-IMF. XI. The sample of hot core candidates: A rich population of young high-mass protostars unveiled by the emission of methyl formate - Bonfand, M. (2024)
Context. The star formation process leads to an increased chemical complexity in the interstellar medium. Sites associated with highmass star and cluster formation exhibit a so-called hot core phase, characterized by high temperatures and column densities of complex organic molecules. Aims. We aim to systematically search for and identify a sample of hot cores toward the 15 Galactic protoclusters of the ALMA-IMF Large Program and investigate their statistical properties. Methods. We built a comprehensive census of hot core candidates toward the ALMA-IMF protoclusters based on the detection of two CH3OCHO emission lines at 216.1 GHz. We used the source extraction algorithm GExt2D to identify peaks of methyl formate (CH3OCHO) emission, a complex species commonly observed toward sites of star formation. We performed a cross-matching with the catalog of thermal dust continuum sources from the ALMA-IMF 1.3 mm continuum data to infer their physical properties. Results. We built a catalog of 76 hot core candidates with masses ranging from ∼0.2 M⊙ to ∼80 M⊙, of which 56 are new detections. A large majority of these objects, identified from methyl formate emission, are compact and rather circular, with deconvolved full width at half maximum (FWHM) sizes of ∼2300 au on average. The central sources of two target fields show more extended, but still rather circular, methyl formate emission with deconvolved FWHM sizes of ∼6700 au and 13 400 au. About 30% of our sample of methyl formate sources have core masses above 8 M⊙ and range in size from ∼1000 au to 13 400 au, which is in line with measurements of archetypical hot cores. The origin of the CH3OCHO emission toward the lower-mass cores may be explained as a mixture of contributions from shocks or may correspond to objects in a more evolved state (i.e., beyond the hot core stage). We find that the fraction of hot core candidates increases with the core mass, suggesting that the brightest dust cores are all in the hot core phase. Conclusions. Our results suggest that most of these compact methyl formate sources are readily explained by simple symmetric models, while collective effects from radiative heating and shocks from compact protoclusters are needed to explain the observed extended CH3OCHO emission. The large fraction of hot core candidates toward the most massive cores suggests that they rapidly enter the hot core phase and that feedback effects from the forming protostar(s) impact their environment on short timescales.